2016
DOI: 10.1038/cdd.2016.83
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of TAp73 inhibition by ΔNp63 and structural basis of p63/p73 hetero-tetramerization

Abstract: Members of the p53 tumor-suppressor family are expressed as multiple isoforms. Isoforms with an N-terminal transactivation domain are transcriptionally active, while those ones lacking this domain often inhibit the transcriptional activity of other family members. In squamous cell carcinomas, the high expression level of ΔNp63α inhibits the tumor-suppressor function of TAp73β. This can in principle be due to blocking of the promoter or by direct interaction between both proteins. p63 and p73 can heterooligomer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 35 publications
(49 reference statements)
2
40
0
Order By: Relevance
“…Consistently, PpIX was shown to induce cancer cell death in sarcoma cells 25 . In line with our data (Figure 1d Recently, detailed analysis of the oligomeric state of TAp73 alpha by Melino and Dötsch labs revealed a high structure homology between p53 and p73 tetramers 26 .…”
Section: Discussionsupporting
confidence: 92%
“…Consistently, PpIX was shown to induce cancer cell death in sarcoma cells 25 . In line with our data (Figure 1d Recently, detailed analysis of the oligomeric state of TAp73 alpha by Melino and Dötsch labs revealed a high structure homology between p53 and p73 tetramers 26 .…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, previous studies demonstrated the mechanistic action of ΔNp63α in SCC . For example, ΔNp63α inhibits the activity of TAp73 via transcriptional inhibition and, to a lesser extent, direct interaction between both proteins . Therefore, attenuation of ΔNp63α nuclear transport can serve as a new strategy to compromise its functions.…”
Section: Discussionmentioning
confidence: 96%
“…p53 family can be considered among the most powerful family of genes for the wide range of functions covering from tumour suppression, homeostasis and development [1][2][3][4][5][6][7][8][9][10][11]. In this context the p53 family member p73 plays critical roles such as tumour suppression [12][13][14][15][16][17], neuronal development and differentiation [18][19][20][21][22][23][24], metabolic control [25][26][27][28][29][30][31][32][33], and spermatogenesis and the maintenance of male and female fertility [34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%